2019
DOI: 10.3390/nu11102335
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Inadequacy in Short Sleep: Analysis of the NHANES 2005–2016

Abstract: One third of U.S. adults report short sleep (<7 h), which has been linked to negative health outcomes. Inadequate intake of micronutrients across the U.S. adult population has been reported, and a relationship between sleep conditions and micronutrient intake is emerging. This cross-sectional analysis of the National Health and Nutrition Examination Survey (NHANES 2005–2016) (n = 26,211) showed that participants with short sleep duration had a lower usual intake (Food + Supplements) of calcium, magnesium, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 52 publications
1
39
0
8
Order By: Relevance
“…Ikonte et al reported that participants in the NHANES 2005-2016 who slept ≤7 h per night had lower usual intakes of magnesium compared to all adults, 19+ years, even after adjusting for all covariates. In both young (19-50 y) and older (51-99 y) women, they also found short sleep duration to be associated with prevalence of inadequate intakes of magnesium and 10 other micronutrients [61].…”
Section: Previous Studiesmentioning
confidence: 93%
“…Ikonte et al reported that participants in the NHANES 2005-2016 who slept ≤7 h per night had lower usual intakes of magnesium compared to all adults, 19+ years, even after adjusting for all covariates. In both young (19-50 y) and older (51-99 y) women, they also found short sleep duration to be associated with prevalence of inadequate intakes of magnesium and 10 other micronutrients [61].…”
Section: Previous Studiesmentioning
confidence: 93%
“…Research, Society and Development, v. 9, n. 11, e57791110238, 2020 (CC BY 4. Research, Society and Development, v. 9, n. 11, e57791110238, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.10238 excluídos pois não apresentavam interposição com a pergunta norteadora. Dos seis estudos restantes, dois foram excluídos por ser uma revisão sistemática, sendo então admitidos para a análise final quatro artigos (Grandner, et al, 2010;Yackobovitch-Gavan et al, 2018;Ikonte et al, 2019;Hashimoto et al, 2020) O primeiro estudo (Grandner, et al, 2010) "Quantas horas de sono você costuma dormir à noite nos dias de semana ou de trabalho? ", com duração curta do sono definida como menos de 7 horas por noite.…”
Section: Resultsunclassified
“…The National Health and Nutrition Examination Survey (NHANES) is a bi-yearly cross-sectional study of the US population conducted by Centers for Disease Prevention and Control (CDC). Data from the 2005-2016 (2005-2006, 2007-2008, 2009-2010, 2011-2012, 2013-2014, and 2015-2016) NHANES was previously analyzed [10]. Details regarding the study participants, demographics, methods, statistical analyses are described by Ikonte et al [10].…”
Section: Methodsmentioning
confidence: 99%
“…Data from the 2005-2016 (2005-2006, 2007-2008, 2009-2010, 2011-2012, 2013-2014, and 2015-2016) NHANES was previously analyzed [10]. Details regarding the study participants, demographics, methods, statistical analyses are described by Ikonte et al [10]. Briefly, the usual intake, % of population below EAR and % of population above the UL were analyzed using two reliable 24 h dietary recall interviews in 26,282 adults aged 19-99 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation